Undergoing radical treatment for prostate cancer and its impact on wellbeing: A qualitative study exploring men's experiences. - Neel Vyas; Oliver Brunckhorst; Louis Fox; Mieke Van Hemelrijck; Gordon Muir; Robert Stewart; Prokar Dasgupta; Kamran Ahmed (PLoS ONE)
Introduction Quality of life in prostate cancer survivorship is becoming increasingly important, with mental and social wellbeing recognised as key components. However, limited global evaluation of psychosocial challenges experienced after treatment exists. Therefore, we aimed to explore the lived experiences of men who underwent radical treatment, and its psychosocial impact. Material and methods This qualitative study was conducted using 19 men who had undergone radical treatment (prostatectomy or radiotherapy) for their cancer. Semi-structured interviews were conducted exploring lived experiences of men after treatment. A Structured thematic analysis of collected data was undertaken, with an inductive co-construction of themes through the lens of the biopsychosocial model. Themes generated were considered within a psychological, social, and physical wellbeing framework. Results An initial knowledge gap meant mental wellbeing was strongly impacted initially leading to a 'Diagnostic Blow and the Search for Clarity'. Doubt over individuals' future resulted in 'An Uncertain Future' in many men. Once treatment was completed a 'Reflective journey' began, with men considering their outcomes and decisions made. Social wellbeing was also impacted with many identifying the 'Emotional Repercussions' on their relationships and the impact their diagnosis had on their partner and family. Many subsequently sought to increase their support through 'The Social Network and Advocacy', while physical changes led to an increased need for 'Social Planning'. Finally, physical wellbeing was highlighted by a continual acknowledgement of the 'Natural process of ageing' leading to a reluctancy to seek help, whilst simultaneously attempting to improve existing health via 'The Health Kick'. Conclusions Radical treatments have a considerable impact on mental and social wellbeing of individuals. Anxiety after diagnosis and significant uncertainty over individual futures exist, with physical complications of treatment leading to social repercussions. Future research should aim to identify forms of support to improve quality of life of these men.